Measuring the impact of agriculture programs on diets and nutrition - Leroy, Jef L.; Ruel, Marie T.; Olney, Deanna K. (International Food Policy Research Institute, 2020)
Agriculture holds tremendous potential to improve nutrition. Traditionally, agriculture investments focused on producing enough food to allow people to meet their caloric needs and on generating employment and income. In the last decade, the understanding of how agriculture can contribute to nutrition has shifted from the implicit assumption that increased productivity and income would automatically improve nutrition to the acknowledgement that explicit nutrition goals and actions are needed to improve nutritional outcomes (1–4). This has led to increased commitments and investments in nutrition-sensitive agriculture programs and accompanying research to study these programs’ impact on nutrition outcomes. Guidance on how to make agriculture more nutrition-sensitive was also developed and included recommendations to target the first 1,000 days of a child’s life (from conception to 2 years of age) and to focus on reducing stunting (5–7). These developments coincided with the global commitment to achieve the World Health Assembly target of reducing child stunting by 40 percent by 2025 (8).